(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Transcutaneous electrical nerve stimulation (TENS) is not therapeutic cure that works by activating complex neural network and engaging inhibitory descending processes in the central nervous system to diminish hyperalgesia . Neuromuscular electrical stimulation (NMES) have recommended as supplement for other treatments, such as workout, or as a stand-alone treatment to increase muscle power, decrease knee discomfort, and improve function. NMES may be an alternate treatment for people who are unable or unable to engage in full-body exercise to strengthen upper limb muscles. Patients appear to like NMES programmer, which have resulted with advancement in muscle work, physical exercise strength, and wholesomeness. The widespread utilisation of [TENS] Transcutaneous Electrical Nerve Stimulation to alleviate injury is based on pain suppression by extra somatosensory information. High-frequency [50-100 Hz] and of less-intensity 'traditional' TENS, and less-frequency [2-4 Hz] and more-intensity 'acupuncture-like' TENS, both cause analgesia in animal models.